Gerakan Masyarakat Anti Jentik (Gemantik) Di Kelurahan Baning Kota Sintang - Nurul Khoirun Nisa; Aditiya Sardi; Zuliani Zuliani; Sunarti Sunarti; Ria Damayanti (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by a virus and spread by vectors. The virus that causes dengue fever is dengue, while the vector that transmits it comes from the Aedes aegypti and Aedes albopictus mosquitoes. DHF is not a new disease because this disease occurs almost every year. Especially when there is a change in season from the rainy season to the dry season or vice versa (Dewi et al., 2019). Dengue Hemorrhagic Fever (DHF), which is usually called Dengue Haemorrhagic Fever (DHF), is one of several infectious diseases that is a health problem in the world, especially in developing countries.